X-ray Nanochemistry Concepts and Development - Guo, Ting.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book describes the latest developments in the new research discipline of X-ray nanochemistry, which uses nanomaterials to enhance the effectiveness of X-ray irradiation. Nanomaterials now can be synthesized in such a way as to meet the demand for complex functions that enhance the X-ray effect. Innovative methods of delivering the X-rays, which can interact with those nanomaterials much more strongly than energetic electrons and gamma rays, also create new opportunities to enhance the X-ray effect. As a result, new concepts are conceived and new developments are made in the last decade, which are discussed and summarized in this book. This book will help define the discipline and encourage more students and scientists to work in this discipline. These efforts will eventually lead to formation of a full set of physical, chemical and materials principles for this new research field.
Part I. Introduction -- Chapter 1.X-ray Nanochemistry: Background and Introduction -- Part II. Concepts -- Chapter 2.Physical Principles and Physical Enhancement -- Chapter 3.Chemical Enhancement -- Chapter 4.Biological Enhancement -- Chapter 5.Isolation, Optimization and Combination of Individual Enhancements -- Part III. Nanomaterials and Methods -- Chapter 6.Nanomaterials for X-ray Nanochemistry -- Chapter 7.Techniques and Instruments for X-ray Nanochemistry -- Part IV. Development of Applications -- Chapter 8. X-ray Nanochemistry and Its Applications in Biology -- Chapter 9.Medical Applications of X-ray Nanochemistry -- Chapter 10.Applications of X-ray Nanochemistry in Catalysis -- Chapter 11. Applications of X-ray Nanochemistry in Sensing, Radiolysis and Environmental Research -- Part V. Conclusions and Future Work -- Chapter 12.Conclusions and Future Work. .
Keywords: Nanochemistry; Spectrum analysis; Materials -- Analysis; Nanochemistry; Spectroscopy; Characterization and Analytical Technique